Strategies for Managing Information and Communication Technology Infrastructure in the Implementation of Computer-Based National Assessments at Elementary Madrasahs - Irwan Nurjamiludin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The research is motivated by the importance of ICT readiness in supporting ANBK, particularly in schools located in under-resourced rural areas. This study aims to explore the management of information and communication technology (ICT) infrastructure, the implementation of the Computer-Based National Assessment (ANBK), and the ICT management strategies applied at MI Amanah Bangunjaya. The study adopts a qualitative approach using a case study method. Data were collected through participatory observation, in-depth interviews, and documentation. The research subjects included the school principal, teachers, proctors, technicians, and students at MI Amanah Bangunjaya. The findings indicate that ICT infrastructure management at MI Amanah Bangunjaya is fairly well implemented despite several obstacles, such as a limited number of computers, unstable internet connections, and the absence of standard operating procedures for technical issues. Nevertheless, the school managed to carry out the ANBK effectively by dividing exam sessions, collaborating with other institutions, and conducting technical training for proctors and technicians. The strategies adopted were adaptive and practical but lacked long-term strategic planning. The study concludes that strengthening ICT infrastructure management, developing standard operating procedures, and providing regular training for human resources are crucial to ensure a more optimal, efficient, and sustainable implementation of ANBK in the future. These findings are expected to serve as a reference for other educational institutions in developing more effective ICT management strategies.